Outcomes of ovarian cancer in young women in Hospital Tengku Ampuan Afzan, Kuantan Malaysia: 2006-2012 - Awang, Mokhtar (2013)
The study was carried out to examine the clinicalpathological characteristics, the treatment modalities and outcomes of ovarian cancer in the young women.